1999
DOI: 10.5326/15473317-35-1-13
|View full text |Cite
|
Sign up to set email alerts
|

Complications and mortality associated with anesthesia in dogs and cats

Abstract: The complications and mortality associated with anesthesia of dogs and cats in a university teaching hospital were determined. During one year, 2,556 dogs and 683 cats were anesthetized by the anesthesia service. Hypotension occurred in 179 (7%) dogs and 58 (8.5%) cats. Cardiac dysrhythmias occurred in 64 (2.5%) dogs and 12 (1.8%) cats. Transfusions were required in 31 (1.2%) dogs. Hypercapnea occurred in 33 (1.3%) dogs and one (less than 1%) cat. Hypoxemia occurred in 14 (0.5%) dogs. Anesthetic complications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
150
3
10

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(201 citation statements)
references
References 4 publications
10
150
3
10
Order By: Relevance
“…In the current study population, hemodynamic changes during general anesthesia were common, as is reported widely in veterinary medicine (Table 1). 27, 28, 29 Episodes of bradycardia were recorded in 69.4% of dogs, recently reported to be a common finding in miniature Dachshunds, the most common breed in the current study 44. Our regression tree analysis highlighted a possible association between duration of bradycardia and OFS improvement in grade 3 or 4 dogs (Fig 1).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the current study population, hemodynamic changes during general anesthesia were common, as is reported widely in veterinary medicine (Table 1). 27, 28, 29 Episodes of bradycardia were recorded in 69.4% of dogs, recently reported to be a common finding in miniature Dachshunds, the most common breed in the current study 44. Our regression tree analysis highlighted a possible association between duration of bradycardia and OFS improvement in grade 3 or 4 dogs (Fig 1).…”
Section: Discussionsupporting
confidence: 58%
“…Hypotension secondary to reduced systemic vascular resistance or decreased cardiac output due to bradycardia occurs commonly under general anesthesia in dogs 27, 28, 29. As a result, it is possible that dogs undergoing surgical decompression to treat thoracolumbar IVDE could be exposed to hemodynamic changes that could affect functional recovery.…”
mentioning
confidence: 99%
“…The second notable difference, and arguably the most clinically relevant, was a lack of hypotension during OFA. Hypotension is one of the most common complications of anaesthesia (Gaynor et al 1999). Increase in blood pressure can be a sign of sympathetic response to surgical stimulation.…”
Section: Casementioning
confidence: 99%
“…Cats and dogs are frequently subjected to general anaesthesia for any type of surgical procedure (Gaynor et al, 1995). General anaesthesia is a state of unconsciousness and loss of protective reflexes resulting from the administration of one or more anaesthetic agents (Dewachter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%